Prototype Sterilisasi Virus Barang Belanjaan Online Berbasis Arduino - Ashari, Maulana; Zaen, Mohammad Taufan Asri; Putri, Juliyantika Ayudita; Imtihan, Khairul; Bagye, Wire (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
In this study, efforts were made to break the chain of spread of COVID-19 with the main technique of heating to dry the liquid on the surface of the groceries. Built a heating box with a length of width and height of 65cm using the main material of fiber glass with a thickness of 3mm. By using Arduino Uno as a control tool, the MLX temperature sensor is used to measure the temperature in the box and the Proximity sensor is used as a sensor to detect goods. The method used to design the tool is the Research and Development (R&D) method. The test results using an initial temperature of 47º and the desired temperature of 56ºC takes 07 minutes 21 seconds the temperature displayed by the LCD has reached 56ºC, when the surface temperature of the goods is measured using a thermogun, the results are 43.1ºC. Complete trial using an initial temperature of 29ºC and the desired temperature of 56ºC takes 2 minutes 18 seconds, the temperature displayed on the LCD has reached 56ºC. When the surface temperature of the goods is measured using a thermogun, the results are 55.5ºC. The results of the last test show that the temperature is close to 56ºC.